Equivalent Cauchy Sequences in q1,q2-Quasi Metric-Like Space and Applications to Fixed-Point Theory - Eriola Sila; Sidite Duraj; Elida Hoxha (Journal of Mathematics)
This paper introduces the concept of q1,q2-quasi metric-like space X,p and delves into some topological properties of it. A necessary and sufficient condition related to equivalent Cauchy sequences and Cauchy sequences in X,p have been proved. Furthermore, the results of the fixed point are shown in the setting of q1,q2-quasi metric-like space as applications of conditions of equivalent Cauchy sequences. Besides, some instances are inclined to epitomize the examined consequences.